Drip Irrigation in Castor: A Potential Boon to Western Rajasthan - Jangir, Rameti; Shekhawat, Kapila; Kumawat, Rekha; Jeberson, M. Samuel (Chronicle of Bioresource Management, 2025)
Agriculture in western Rajasthan faces severe challenges due to acute water scarcity, erratic rainfall, high evaporation, and over-exploited groundwater. Castor (Ricinus communis L.), a drought-tolerant oilseed crop which thrives well in arid conditions, but meeting out the water requirement optimizes yields. Among the methods of irrigation application, drip irrigation is an efficient water supply technology which ensures consistent soil-moisture by delivering water directly to the plant roots, enhancing efficiency by 50% and increasing yield by 20-40%. This article aims to simplify the use, protocols and benefits of the adoption of drip irrigation in castor cultivation for farmers in water-scarce regions like western Rajasthan. It provides practical and accessible guidelines, including detailed layout plans and tips, to help farmers confidently install and manage drip systems. By elucidating the technology, the article empowers farmers to enhance water-use efficiency, improve productivity, and achieve sustainable farming practices.